Financial management - Wright, M. G. (London : New York, McGraw-Hill, 1970)
The book examines the role of financial management beyond a mere description by institution. The book further suggests some of the benefits of financial management to business and institutional management.
include index
Bibliography: p. 284-285.
asm; 27/02/19
Loans
Keywords: Finance; Corporations